Virological outcomes of third-line antiretroviral therapy in a global context: a systematic reviews and meta-analysis - Tegene Atamenta kitaw; Biruk Beletew Abate; Gizachew Yilak; Befkad Derese Tilahun; Abebe Merchaw Faris; Getachew Tesfaw Walle; Ribka Nigatu Haile (AIDS Research and Therapy, 2024)
Abstract Background Despite remarkable progress, HIV’s influence on global health remains firm, demanding continued attention. Understanding the effectiveness of third-line antiretroviral therapy in individuals who do not respond to second-line drugs is crucial for improving treatment strategies. The virological outcomes of third-line antiretroviral therapy vary from study to study, highlighting the need for robust global estimates. Methods A comprehensive search of databases including PubMed, MEDLINE, International Scientific Indexing, Web of Science, and Google Scholar, was conducted. STATA version 17 statistical software was used for analysis. A random-effects model was applied to compute the pooled estimates. Subgroup analysis, heterogeneity, publication bias, and sensitivity analysis were also performed. The prediction interval is computed to estimate the interval in which a future study will fall. The GRADE tool was also used to determine the quality of the evidence. Results In this systematic review and meta-analysis, 15 studies involving 1768 HIV patients receiving third-line antiretroviral therapy were included. The pooled viral suppression of third-line antiretroviral therapy was 76.6% (95% CI: 71.5- 81.7%). The viral suppression rates at 6 and 12 months were 75.5% and 78.6%, respectively. Furthermore, third-line therapy effectively suppressed viral RNA copy numbers to ≤ 50 copies/mL, ≤ 200 copies/mL, and ≤ 400 copies/mL with rates of 70.7%, 85.4%, and 85.7%, respectively. Conclusion More than three-fourths of patients on third-line antiretroviral therapy achieve viral suppression. Consequently, improving access to and timely initiation of third-line therapy may positively impact the quality of life for those with second-line treatment failure.